Characteristics of sheep marketing channels in Morocco, Algeria and Tunisia - Boulanouar B.; Elloumi M.; Khelil M.; Mekersi S.; Selmi S.; Alary V.; Boutonnet J.P. (Changes in sheep and goat farming systems at the beginning of the 21st century : research, tools, methods and initiatives in favour of a sustainable development, 2009)
In North Africa, very few studies dealt with livestock and meat marketing channels. In order to contribute to covering this gap, surveys were conducted Moroccan, Algerian and Tunisian rural communities. Additionally, and in order to describe the role of different actors in the marketing channels, other surveys were organized in several animal markets. The objective was to reconstruct the different pathways through which sheep move from producers to consumers and understand transactions' modalities. This first hand descriptive analysis helped gaining insights on sheep marketing channels and strategies adopted by farmers, traders' characterization, price and margin formation and meat consumption trends. The paper emphasizes also distinctive and common features across the three countries. Meat market analysis revealed the beginning of a price differentiation according to market and consumer types, season and social event and finally by the recent development of super markets that provide new types of meat cuts. These changes could influence distribution channels with the emergence of differentiated whole carcass sales with different pieces targeting different socio-economic niches. The present research faced some difficulties of reliable data availability as it is the case of the Algerian trans-border informal transactions towards Tunisia and Morocco. This study is first hand description of sheep marketing channels in North Africa with a preliminary understanding of sheep and meat marketing channels and transactions in the three communities studied. Up scaling such research to include a larger and a more comprehensive sampling is necessary in order to gain more representation of different realities and gathering more accurate and reliable data.
Proceedings of the Seminar of the Subnetwork on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2007/11/15-17, Ponte de Lima (Portugal)